P05.19 Hippocampal N - acetylaspartate concentration correlates to verbal memory before radiotherapy for brain metastases. (19th September 2018) - Jancalek, R; Solar, P; Pospisil, P; Bulik, M; Burkon, P; Hynkova, L; Slampa, P; Sana, J; Slaby, O; Kazda, T
Abstract: Background: Changes of quality of life and cognitive function (especially verbal memory) after brain radiotherapy is currently widely discussed in neurooncology with substantial change in the paradigm of treatment of patients with brain metastases. In our previous prospective study, we described a decrease in the hippocampal concentration of N-acetylaspartate (NAA, marker of neuronal density and viability) in response to whole brain radiotherapy (WBRT). These changes may be at least partially responsible for subsequent memory impairment. The aim of presented secondary analysis is to evaluate the baseline NAA concentration (ie, before radiotherapy) in all enrolled patients and to describe the relation to the baseline verbal memory. Material and Methods: Patients with brain metastases indicated to WBRT underwent hippocampal MR spectroscopy (MRS) along with neuropsychological examinations focused among others to verbal memory. The areas of interest in MRS were temporal lobes, the voxel layer was adapted to the area of hippocampus. A specialized java Spectroscopic Imaging Processing Software (jSIPRO) was used to calculate the absolute [mM] NAA concentrations in individual voxels. Verbal memory was evaluated using the Auditory Verbal Learning Test with the main subtest being total recall (AVLT_TR). Absolute NAA concentrations for right and left hippocampus and the sum of absolute NAA concentrations in both hippocampi were correlated to results of AVLT_TR. Results: The examination was performed in 26 patients. Patients were divided into two groups based on median NAA concentration (8.56 mM). The median AVLT_TR was 37 points in the group with hippocampal NAA concentration ˂8.56 mM. In the group of patients with baseline NAA concentration ≥ 8.56 mM, the median AVLT_TR was higher with 43 points (Mann-Whitney U Test, p = 0.02). Conclusion: Non-invasive examination by hippocampal MRS can predict the baseline preradiotherapy cognitive functions (the most important domain in relation to radiotherapy of brain metastases is verbal memory), which are normally tested by time-consuming and difficult for patients psychological tests. Patients in our cohort who had lower baseline NAA hippocampal concentrations had a significantly lower baseline verbal memory. NAA hippocampal concentrations may be a useful biomarker for selecting patients who would benefit most from the subsequent special radiotherapy techniques such as hippocampal sparing WBRT or other procedures reducing the risk of iatrogenic deterioration of quality of life in patients treated with a palliative intent, especially in cases where local brain stereotactic radiotherapy is not applicable or available.